2004
DOI: 10.1289/ehp.6655
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic-induced enhancement of ultraviolet radiation carcinogenesis in mouse skin: a dose-response study.

Abstract: New cancer rates exhibited a consistent-with-linear dependence on time beginning after initial cancer-free intervals ranging between 88 and 95 days. Epidermal hyperplasia was elevated by arsenite alone and UVR alone and was greater than additive for the combined exposures as were growth rates of the cancers. These results demonstrate the usefulness of a new animal model for studying the carcinogenic action of dietary arsenite on skin exposed to UVR and should contribute to understanding how to make use of anim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
92
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(95 citation statements)
references
References 37 publications
3
92
0
Order By: Relevance
“…However, we have no explanation for why this protective effect was observed only among men, although it is possible that the gender interaction is a marker for some unmeasured exposure that occurs more frequently in men than in women. For example, some recent animal studies have shown an interaction between arsenic and UV in the development of skin lesions (46,47).…”
Section: Discussionmentioning
confidence: 99%
“…However, we have no explanation for why this protective effect was observed only among men, although it is possible that the gender interaction is a marker for some unmeasured exposure that occurs more frequently in men than in women. For example, some recent animal studies have shown an interaction between arsenic and UV in the development of skin lesions (46,47).…”
Section: Discussionmentioning
confidence: 99%
“…Other animal studies indicate that in skin inorganic arsenic acts as an enhancer with other carcinogens. Thus in mice sodium arsenite (≥1.25 mg/L in drinking water) is cocarcinogenic with solar ultraviolet (UV) light (Rossman et al, 2001, Burns et al, 2004 and arsenate (25 mg/L in drinking water ad libitum for a period of 25 weeks) is cocarcinogenic with 9,10 dimethyl 1-2-benzanthracene (DMBA) (Motiwale et al, 2005). …”
Section: Inorganic Arsenicmentioning
confidence: 99%
“…Tumors occurring in mice given UVR plus arsenite appeared earlier (time to first tumour < 60 d vs > 80 d after UVR exposure alone) and were much larger than in mice given UVR alone. Mice, Skh-1 (F) 182 d Burns et al (2004) Number at start (NR) Mice were fed sodium arsenite continuously in drinkingwater starting at 21 d of age at concentrations of 0.0, 1.25, 2.5, 5.0, and 10 mg/L. At 42 d of age, solar spectrum UVR exposures were applied every other d (3 ×/wk) to the dorsal skin at 1.0 kJ/m 2 per exposure until the experiment ended at 182 d.…”
Section: Target Organ Incidence And/or Multiplicity Of Tumours (%) Comentioning
confidence: 99%
“…PKCε transgenic mice were observed to be highly sensitive to the development of papilloma-independent metastatic squamous cell carcinomas elicited by repeated exposure to UVR (Wheeler et al, 2004(Wheeler et al, , 2005. In studies using Skh-1 mice, exposure to UVR induced a statistically significant increase in the number of malignant skin tumours per mouse, mainly SCCs when compared to controls (Rossman et al, 2002;Burns et al, 2004;Davidson et al, 2004;Uddin et al, 2005Uddin et al, , 2007. Dietary polyunsaturated fat enhances the development of UVR-induced tumours in Skh-1 mice, this enhancement being mediated by a modulation of the immunosuppression caused by chronic UV irradiation (Reeve et al, 1996).…”
Section: Target Organ Incidence And/or Multiplicity Of Tumours (%) Comentioning
confidence: 99%